Investigating the Agreement of Hypomagnesemia Diagnosis in Three Perimeter of Serum, Urine, and Red Blood Cell in Intensive Care Unit: Pilot Study - Nastaran Nazarzade; Mojtaba Mojtahedzadeh; Farshid Gholami; Amirmahdi Mojtahedzadeh; Maryam Shiehmorteza; Amirhossein Ghanbarzamani (Archives of Anesthesia and Critical Care)
Background: Magnesium is a vital element in the body involved in biochemical and physiological processes. Magnesium deficiency can lead to serious consequences including cardiac, neurological, muscular disorders, and other clinical manifestations. In our country, commonly, magnesium measurement is done by measuring serum magnesium levels. This paper discusses the prevalence and consequences of magnesium deficiency in patients hospitalized in the ICU and emphasizes the importance of diagnosis and treating hypomagnesemia. Methods: Diagnosis of hypomagnesemia is done by measuring serum magnesium, urine magnesium, and magnesium in RBCs. We conducted a prospective study on 30 critically ill patients (14 male, and 16 female) who were admitted to the ICU to examine the prevalence of magnesium deficiency. In eligible patients, after measuring serum and RBC magnesium levels, 7.5 grams of magnesium sulfate in 1000 ml isotonic saline was infused over 8 hours at a rate of 125 ml/hour and urine was collected for 24 hours from the start of the infusion. Results: The mean age was 71. There was a significant difference between the levels of serum Mg and RBC Mg (U statistic = 266 and P<0.05). The results showed a significant difference between the levels of serum Mg and urinary Mg (U statistic was almost 0 and P<0.05). The results indicated a significant difference between the levels of urinary Mg and RBC Mg (U statistic was almost 0 and P<0.05). Conclusion: There is no correlation between serum magnesium and the body’s magnesium requirement in patients, and serum magnesium does not reflect the actual status of patients in the ICU. Therefore, measuring the level of magnesium in red blood cells is preferable to urinary magnesium and serum magnesium to investigate hypomagnesemia in the ICU. Additionally, there is no correlation between age, gender, APACHE II score, and the percentage of infused magnesium absorption in patients.